Development of E-LKPD Based on A Scientific Approach for Students of MAN 2 Model Medan - Razid Ananda Siregar (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to develop an E-LKPD based on a scientific approach at MAN 2 Model Medan. The results of this study are in the form of an Electronic Student Worksheet (E-LKPD). Data collection using validation questionnaires, practical questionnaires, student activity sheets, and student response questionnaires to E-LKPD based on a scientific approach. The trial of the E-LKPD was carried out face-to-face in Class X-4 at the MAN 2 Model school. The results of this development research are an E-LKPD based on a scientific approach for students of MAN 2 Model Medan showing that: (1) The E-LKPD developed is stated to be valid based on the assessment of experts and math teachers with an average validity rating of 84.23% with a score